Synthesis of Holmium-Oxide Nanoparticles for Near-Infrared Imaging and Dye-Photodegradation - Zhu, Jia; Shao, Xue-Jun; Li, Zongan; Lin, Chia-Hui; Wang, Cheng-Wan-Qian; Jiao, Keran; Xu, Jian; Pan, Hong-Xia; Wu, Ye (Molecules (Basel, Switzerland), 2022)
The development of multifunctional nanomaterials has received growing research interest, thanks to its ability to combine multiple properties for severing highly demanding purposes. In this work, holmium oxide nanoparticles are synthesized and characterized by various tools including XRD, XPS, and TEM. These nanoparticles are found to emit near-infrared fluorescence (800–1100 nm) under a 785 nm excitation source. Imaging of the animal tissues was demonstrated, and the maximum imaging depth was found to be 2.2 cm. The synthesized nanoparticles also show the capability of facilitating dye (fluorescein sodium salt and rhodamine 6G) degradation under white light irradiation. The synthesized holmium oxide nanoparticles are envisioned to be useful for near-infrared tissue imaging and dye-degradation.